Resource allocation strategies in the reproductive organs of Fagaceae species. Issue 2 (3rd August 2022) - Wang, Yufei; Han, Qingmin; Kitajima, Kaoru; Kurokawa, Hiroko; Shimada, Takuya; Yamaryo, Tamaho; Kabeya, Daisuke; Kawasaki, Tatsuro; Satake, Akiko
Abstract: Allocation strategies of carbon (C), nitrogen (N), and phosphorus (P) are key to the reproductive processes of plants. Nutrient allocation to seeds depends on defensive traits of seeds and fruit because greater nutritional contents attract more seed predators. To compare resource allocation strategies for reproductive and defensive traits across species, we calculated the cost of resource investment in reproductive organs for nine species from four genera and defensive traits for seven species from two genera of Fagaceae. The results showed that no single element is the common resource currency across species, but that the reproductive strategy of each species is regulated by C, N, or P. Reproduction in Fagus crenata was limited by N but not by C, whereas in Quercus serrata it was co‐limited by C and N. Among the seven Fagaceae species, there was a negative correlation between the thickness of the pericarp and the concentration of the total phenolics in the seed and pericarp, suggesting alternative strategies for developing defensive traits in ripening seeds with limited C‐based resources. Overall, our results highlighted the diversity of resource allocation strategies to reproduction and defensive traits of Fagaceae species. To better understand the masting phenomenon at the population or community levels, comprehensive consideration of the diversity of resource allocation strategies among species is worth exploring in the future. Abstract : C, N, P resource in different reproductive organs among Fagaceae species.